Correlation between Forced Vital Capacity and Hemoglobin to VO2 Maximum on People with Yoga Practice - Maria Mumtaz; Kiyatno .; Selfi Handayani (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background: Yoga is one of sport which affect VO2 maximum. The research objective was to determine the relationship between Forced Vital Capacity and hemoglobin to VO2 maximum on people with Yoga practice. This research also concern on comparing the contribution of Forced Vital Capacity and Hemoglobin value in affecting VO2 maximum. Methods: Thisresearch was a cross-sectional observational analytic. It had been done at Ganep Yoga and Ester Yoga on June to August, 2014. Population are all woman who practice Yoga in Ganep and Ester Yoga. The data were collected by using random sampling method. All responden had to fill informed concern and question related to their health condition. Forced vital capacity was measured with spirometer. VO2 maximum was measured with step-up test. Hemoglobin was measured with EasyTouch Hemoglobin Meter. The data were analized by Pearson Correlation test and Regresion test with Statistical Product and Service Solution (SPSS) 20.0. Results: There were relation between Forced Vital Capacity and VO2 maximum with r= 0,836 and contribution = 69,88%. There were relation between hemoglobin and VO2maximum with r= 0,883 and contribution = 77,96%. Significance value of VO2 maximum based on Forced Vital Capacity is 0,184 and VO2 maximum based on hemoglobin is 0,155. R value of Regression test in this study is 0,926, this means there is strong relationship between Forced Vital Capacity and hemoglobin to VO2 maximum. Both variable were examined using Pearson correlation test with p result < 0,05. Conclusions: There is a strong positive and significant statistic correlation between Forced Vital Capacity and hemoglobin to VO2 maximum on People who do Yoga practice. Keywords: Forced Vital Capacity, hemoglobin, VO2 maximum, Yoga